2011
DOI: 10.3171/2011.1.focus111
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of unresectable skull base meningiomas with somatostatin analogs

Abstract: Object The standard surgical treatment for meningiomas is total resection, but the complete removal of skull base meningiomas can be difficult for several reasons. Thus, the management of certain meningiomas of the skull base—for example, those involving basal vessels and cranial nerves—remains a challenge. In recent reports it has been suggested that somatostatin (SST) administration can cause growth inhibition of unresectable and recurrent meningiomas. The applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 35 publications
0
40
1
1
Order By: Relevance
“…The list of drugs without a clear benefit for these tumors continues to grow and includes tamoxifen,[14] irinotecan,[15] temozolomide,[16] octreotide,[17], [18] mifepristone,[19] erlotinib,[20] gefitinib,[20] imatinib,[21] and alpha-interferon [22], [23]. Although initial results with hydroxyurea were promising,[24] further studies showed that radiographic response to hydroxyurea in meningiomas is uncommon [25], [26]…”
Section: Discussionmentioning
confidence: 99%
“…The list of drugs without a clear benefit for these tumors continues to grow and includes tamoxifen,[14] irinotecan,[15] temozolomide,[16] octreotide,[17], [18] mifepristone,[19] erlotinib,[20] gefitinib,[20] imatinib,[21] and alpha-interferon [22], [23]. Although initial results with hydroxyurea were promising,[24] further studies showed that radiographic response to hydroxyurea in meningiomas is uncommon [25], [26]…”
Section: Discussionmentioning
confidence: 99%
“…Exenteration with preservation of the eyelids is a suitable solution due to good postoperative healing. Treatment with sandostatin is indicated also for these types of tumours [27].…”
Section: Discussionmentioning
confidence: 99%
“…The somatostatin analogues have demonstrated efficacy in unresectable or recurrent meningiomas. 11 The management of recurrent or anaplastic meningiomas is complicated by aggressive tumor growth and refractoriness to cytotoxic therapies. 12 Responses to temozolomide 13 and irinotecan 14 in clinical trials have been disappointing so far.…”
Section: Discussionmentioning
confidence: 99%